1963
DOI: 10.1037/h0045094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of "anxiety-lessening" instructions and differential set development on the extinction of GSR.

Abstract: Results of previous investigators indicate a failure of "anxiety-lessening" instructions to extinguish a GSR conditioned under long (e.g., 6 sec.) CS-UCS interval conditions. This study observed the effects of such instruction on GSR extinction under conditions varying UCS intensity and number of reinforcements. Results: (a) GSR extinguished more rapidly and to a greater extent under conditions of anxiety-lessening instructions than under conditions of noninstruction, (b) the instruction effect was independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
1

Year Published

1967
1967
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 9 publications
4
23
1
Order By: Relevance
“…The elimination of such stimulation during extinction results not only in the anticipatory GR, but in a "disparity" response when the expected shock is not delivered. These responses do not occur when >Ss are informed about the elimination of the shock before the first extinction trial (Grings and Lockhart, 1963).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The elimination of such stimulation during extinction results not only in the anticipatory GR, but in a "disparity" response when the expected shock is not delivered. These responses do not occur when >Ss are informed about the elimination of the shock before the first extinction trial (Grings and Lockhart, 1963).…”
Section: Discussioncontrasting
confidence: 53%
“…The experiment reported in this paper tests the possibility that the OR can be enhanced simply by instructing the subject to pay attention to the neutral stimulus. Although instructions to the subject have been shown to have a significant effect on various type of conditioned responses (eyelid, McAllister and McAllister, 1958;GSR, Cook and Harris, 1937;Grings and Lockhart, 1963; classical finger withdrawal, Lindley and Moyer, 1961; and instrumental finger withdrawal, Moyer and Lindley, 1962), little attention has been paid to the effects of instructions per se on the enhancement and habituation of the OR.…”
mentioning
confidence: 99%
“…In the placebo response, the administration of a substance or procedure produces an effect on behavior that is determined by an antecedent description of its action and not by its specific effect (Gallimore & Turner, 1977;Grings & Lockhart, 1963;Jospe, 1978;Kirsh, 1985;Pfefferbaum, 1977). An example involves the administration of a nominal pain-relief pill that relieves pain (Rachlin, 1985).…”
Section: Agencies Of Instructionmentioning
confidence: 99%
“…Only a few studies, however, have considered a need for investigating changes in Ss' sets and attitudes that may occur during the conditioning situation. In an experiment involving th" perceptual disparity response, Grings & Lockhart (1963) reported that some Ss tended to overrespond to changed stimulus conditions and to develop a persisting expectation of further change in conditions, often working in opposition to E's instructions. Also, Spence, Rutledge, & Talbott (1963) discussed the importance of the effects the unexpected change in procedure from acquisition to extinction *This paper is based on a thesis completed by the first author under the direction of the second author and submitted to the University of Montana in partial fulfillment of the requirements of the MA degree.…”
mentioning
confidence: 99%